Sliding mode controllers for the regulation of DC/DC power converters - Rui Esteves Araújo (2003)
Sliding mode controllers are derived for the control of the average output voltage in DC/DC power converters. The controller design is carried out on the basis of well-known bilinear models of such circuits. A cascaded control structure is chosen for ease of control realization and to exploit the motion separation property of this power converter. The performance of the proposed sliding mode controllers is tested for the buck and boost converter type. The numerical simulations will demonstrate the efficiency of sliding mode techniques in this field as a powerful alternative to other existing methods.